موقف الفكر الحداثي من الملائكة The Position of Modernist Thought on (the belief) in Angels - Hakki, Mohammad Salih Abdullah; Ahmad, Masitoh; al-Muhammady, Asma Uthman (Department of Usuluddin and Comparative Religion, KIRKHS, IIUM, 2021)
The study aims at shedding the light on the modernist intellectual position on the doctrinal issues in the aspect of al-samʿiyyÉtwhich is related to (the belief) in the angels. Various claims of the modernist thoughts are therefore discussed together with the explanation of the criticism against them. The study adopts the inductive approach in examining the modernists' texts related to the issue of al-samʿiyyÉtand extrapolating their writings and what they have said about it, as well as using the analytical method in an attempt to present and evaluate their statements, arguments, and proofs. The method of critical approach is applied in criticizing the concept of modernity and the thoughts which came from it, and responding to it in accordance with the scientific methodology, rational as well as naqlīapproach. It explains the concept of modernity and presents its definitions and views of modernist scholars related to this issue along with criticisms against them. The study found that modernity presents itself as an alternative philosophy to replace all beliefs, ideas, and previous divines as well as human perceptions of them, and (also) the invalidity of their claims stemming from this basis. The Modernist thought on the issue related to the angels can be divided into two parties: The first party denies the unseen and therefore denies the angels, and the other one believes in the unseen including the issue of al-samʿiyyÉt, but it was interpreted far from its truth.